2021
DOI: 10.1002/admi.202100379
|View full text |Cite
|
Sign up to set email alerts
|

A General Control Strategy to Micropattern Topological Defects in Nematic Liquid Crystals Using Ionically Charged Dielectric Surface

Abstract: materials such as colloids, [1][2][3] blockcopolymers, [4][5][6] and liquid crystals. [7][8][9][10][11] Especially the structural and optical anisotropy in nematic liquid crystals (NLCs) are useful for stimuli-responsive applications. NLCs are characterized by a spontaneous orientational order of elongated molecules, called the director, which is denoted by a unit vector n. The director field is influenced by the surface boundary (anchoring) effect and by external fields such as electric, magnetic fields, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It should be noted that the required voltage to the sample cell, V=2Vcellcosfalse(2πftfalse), for the director reorientation is practically influenced by the resistances and capacitances of the NLC (RLC and CLC) and the polysiloxane layer (Rnormals and Cnormals), which must be considered particularly for RLCRnormals. [ 53 ] Here, Vcell is the effective AC voltage applied to the sample cell. By assuming an equivalent circuit of the sample cell, the frequency dependence of Vcell at the threshold is schematically illustrated in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the required voltage to the sample cell, V=2Vcellcosfalse(2πftfalse), for the director reorientation is practically influenced by the resistances and capacitances of the NLC (RLC and CLC) and the polysiloxane layer (Rnormals and Cnormals), which must be considered particularly for RLCRnormals. [ 53 ] Here, Vcell is the effective AC voltage applied to the sample cell. By assuming an equivalent circuit of the sample cell, the frequency dependence of Vcell at the threshold is schematically illustrated in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of these compounds is that they are readily available and can easily ensure vertical anchoring for various NLCs. As with polydimethylsiloxane (PDMS), SOG surface allows the use of a silane coupling agent by modifying the surface with ultraviolet ozone (UVO) treatment [49]. Also, SOG can be substituted by a commercial silicone resin such as KR-251 (Shin-etsu).…”
Section: Preparing Sample Cellsmentioning
confidence: 99%
“…Geometry of disclinations networks has been theoretically investigated in the literature, sometimes allowing for analytical expressions for the metric tensor [150][151][152]. Several authors have shown the possibility to design arrays of topological linear defects from photopatterning techniques [153][154][155][156][157] and even to manipulate them [158,159]. If this last point opens the possibility to emulate collisions between particles in the 2+1 model, it is even more interesting for the extension of the Deser, Jackiw and 't Hooft model to 3+1 dimensions [70]: matter particles are represented by a gas of piecewise straight string segments that are likely to collide with a higher frequency.…”
Section: B Beyond Cosmic Wedge Disclinationsmentioning
confidence: 99%